2011
DOI: 10.1177/2156869311431612
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy and Belonging

Abstract: There is a paucity of systematic analysis of the relation between sexual activity and mental health. To address this gap, we ask whether sexual activity associates with lower levels of depression among older adults. We hypothesize that sexual activity-especially if it typically incorporates other forms of physical affection-may be a socially meaningful activity and may create intimacy that provides social uplift. We test this hypothesis against alternative hypotheses that relationship characteristics or physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 79 publications
3
16
1
Order By: Relevance
“…The previous literature examined cross-sectional links between sexual satisfaction and depressive symptoms, where our findings expands this link longitudinally and dyadically. Our significant men's and women's own effects were consistent with a previous study that found higher sexual activity was linked with lower depressive symptoms for both men and women (Ganong & Larsoon, 2011), but this link held up across time in our study. To our knowledge, no other study examined partner effects of this link.…”
Section: Relationship Satisfaction and Sexual Satisfactionsupporting
confidence: 92%
See 2 more Smart Citations
“…The previous literature examined cross-sectional links between sexual satisfaction and depressive symptoms, where our findings expands this link longitudinally and dyadically. Our significant men's and women's own effects were consistent with a previous study that found higher sexual activity was linked with lower depressive symptoms for both men and women (Ganong & Larsoon, 2011), but this link held up across time in our study. To our knowledge, no other study examined partner effects of this link.…”
Section: Relationship Satisfaction and Sexual Satisfactionsupporting
confidence: 92%
“…Comparing these results to the existing literature on the general association between sexual satisfaction and depressive symptoms reveal consistency where sexual satisfaction was associated with less depressive symptoms (e.g. Ganong & Larsoon, 2011); and inconsistency with earlier research that found higher sexual satisfaction was associated with greater depressive symptoms (Peleg-Sagy & Shahar, 2013).…”
Section: Relationship Satisfaction and Sexual Satisfactioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Surprisingly, we did not observe similar results for male participants. One potential explanation for this finding is that men, relative to women, tend not to strongly associate sexual activity with emotions (Ganong and Larson 2011;Hiller 2004). It is possible that even male participants who were low in avoidance did not feel strongly about their partner's sexual history (or did care but suppressed the emotion; Marks and Vicary in press), rendering the interaction between participant gender, target gender, and target's number of partners non-significant.…”
Section: Discussionmentioning
confidence: 81%
“…This study, therefore, evaluates the potential changes in health behaviors and their influences on mental health in people socially isolated due to a COVID-19 lockdown. This assessment was partly necessitated by studies (Ganong & Larson, 2011;Shim et al, 2014) that have indicated that mental health decline is a potential consequence of the aforementioned changes in behaviors.…”
Section: Introductionmentioning
confidence: 99%